2014
DOI: 10.1123/tsp.2013-0037
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of Excellence in Elite Sport: Motivational Climate in a World Champion Team

Abstract: This case study focused on the New Zealand All Blacks rugby team during the period from 2004 to 2011, when Graham Henry (head coach) and Wayne Smith (assistant coach) coached and managed the team. More specifically, this case study examined the motivational climate created by this coaching group that culminated in winning the Rugby World Cup in 2011. In-depth interviews were completed with Henry and Smith in March 2012. A collaborative thematic content analysis revealed eight themes, regarding motivational iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 42 publications
3
64
0
2
Order By: Relevance
“…[11] Taylor and Bruner [12] found a negative relationship between psychological need satisfaction and social exclusion in elite youth soccer players of black-and white-English ethnic origin. A team environment in which all players can feel comfortable to express themselves both on and off the field, and believing that they have the support of the team leadership, can only enhance both individual and team performance.…”
Section: So You Buy Into the Talk Of The Team Without Actually Owningmentioning
confidence: 99%
“…[11] Taylor and Bruner [12] found a negative relationship between psychological need satisfaction and social exclusion in elite youth soccer players of black-and white-English ethnic origin. A team environment in which all players can feel comfortable to express themselves both on and off the field, and believing that they have the support of the team leadership, can only enhance both individual and team performance.…”
Section: So You Buy Into the Talk Of The Team Without Actually Owningmentioning
confidence: 99%
“…Therefore, there is a need to study outstanding coaches using more scientific approaches. As an example of an excellent and methodologically rigorous case study, Hodge, Henry and Smith (2014) presented an investigation of Graham Henry and Wayne Smith, head and assistant coaches respectively, of the New Zealand All-Blacks, the most successful rugby franchise of all time. Hodge and his colleagues clearly identified their paradigmatic stance as researchers, used multiple data sources, discussed the researcher as an instrument and enhanced the credibility of their findings by employing member checking, a critical friend and audit trail procedures.…”
Section: Development Of Young Athletes: a Case Study Of J Robinsonmentioning
confidence: 99%
“…In many of the studies coaching philosophies were examined but never explicitly defined, whereby the elements of the coaching philosophy were not delineated nor were specific results of what coaches exactly said about their philosophies (versus coaching strategies) reported. Additionally, as previously stated only a few studies reported steps taken to maintain methodological and conceptual rigor, although Hodge et al (2014) provided an excellent example for doing so.Perhaps the most academically-oriented and rigorous critique of the coaching philosophy literature was conducted by Jenkins (2010). In addition to discussing definitions of coaching philosophy, he outlined three directions for future research.…”
mentioning
confidence: 99%
“…A investigação recente ensina que a tomada de decisão em jogos de equipa se constrói mediante um processo de interacção dinâmico entre o treinador e o atleta, em que este último deve ser estimulado a ser um agente activo na sua própria aprendizagem (Hodge et al, 2014). Por este motivo, algumas federações nacionais têm adoptado as teorias construtivistas nos seus curricula de formação de treinadores, de modo a aperfeiçoar a capacidade de intervenção pedagógica dos seus proissionais, no âmbito da construção do treino e do ensino da tomada de decisão (Reid & Harvey, 2014).…”
Section: Resultsunclassified
“…Este movimento surgiu como alternativa ás metodologias de ensino ditas « tradicionais » que supostamente se focariam no domínio das técnicas (Light, 2013). A razão para a implantação e aceitação generalizada desta conceptualização do treino diferencia-se por dois planos: (i) ao nível da iniciação desportiva, a passagem do controle da progressão pedagógi-ca para o jovem atleta, facilitaria a compreensão do processo por parte do aprendiz, que levaria a maior satisfação com a prática e a redução do abandono (Camiré, Trudel & Forneris, 2014); (b) no alto rendimento, considera-se cada vez mais importante que o atleta seja capaz de, autonomamente, tomar decisões adequadas à situação de competição (Hodge, Henry & Smith, 2014). A principal referência pedagógica no campo é representada pelo modelo Teaching Games for Understanding (TGfU), que inspirou outras experiências e desenvolvimento dos mesmos princípios, tais como Game Sense, Game Centered Approach ou Tactical Learning.…”
Section: Introductionunclassified